Race, Ethnicity, and Official Perceptions in the Juvenile Justice System: Extending the Role of Negative Attributional Stereotypes. (November 2021) - Beckman, Laura; Rodriguez, Nancy
Overrepresentation of youth of color in the juvenile justice system has been well-documented. Although prior research has frequently drawn on attribution theory to explain the sources of racial and ethnic disparity in juvenile court outcomes, the key mechanisms (negative internal and external attributions) put forth by this theory have seldom been directly empirically tested. Using juvenile probation file content ( N = 285) that quantitatively captures court officials' perceptions of youth, this study examines whether negative attributions differentially influence diversion decisions for Black, Latino/a, and Native American youth. Findings reveal that youth of color are more likely to be linked to negative internal attributions in comparison with White youth. Importantly, negative internal attributions in turn decrease the probability of receiving diversion. Analyses demonstrate that negative stereotypes play an important role in how juvenile court officials form perceptions of youth. Implications for theory and practice are discussed.